Diallel analysis and heterosis components in paprika peppers - Lasmar, André; Maluf, Wilson; Ticona-Benavente, César Augusto; Nogueira, Douglas; Nogueira, Danilo (Revista Ciência Agronômica, 2019)
The aim of this study was to quantify and assess the components of heterosis in paprika hybrids related to yield, capsanten pigment content (estimated as ASTA degrees) and resistance to Phytophthora capsici, and to identify parental lines with high general combining ability (GCA) to be used in future breeding programmes and/or to obtain new hybrids. Fifteen hybrids were obtained through a complete diallel cross (reciprocal hybrids excluded) among six proprietary paprika breeding lines from HortiAgro Sementes S.A., four of which originally introduced from Peru (P1=PIM 032-03; P2=PIM 033-11; P3=PIM 034-19; P4=PIM 035-01) and two from the U.S.A. (P5=PIM 036-08; P6=PIM 037-18). Epistatic gene action was involved in the expression of heterosis for fresh and dry yields and carotenoid pigment contents, and heterosis was predominantly in the direction of higher yields. No significant heterosis effects were detected for resistance to P. capsici, and gene action was of incomplete dominance for the resistant phenotype. The parental lines P1 and P5 showed high GCA values for all characters, and may be used in breeding programmes to obtain new improved lines or for the production of higher yielding hybrids. The most promising hybrid was P3xP5, which outperformed the standard cultivar “Papri Queen” in fresh (68 t ha-1) and dry (10 t ha-1) fruit yields and ASTA degrees (157), in addition to being resistant to P. capsici. The parental line P5, as well as the hybrids in which it participated as a parent were assessed as resistant to P. capsici.